Role of subject-specific musculoskeletal loading on the prediction of bone density distribution in the proximal femur - Vahdati, A.; Walscharts, S.; Jonkers, I.; Garcia-Aznar, J.M.; Vander Sloten, J.; van Lenthe, G.H. (Journal of the mechanical behavior of biomedical materials, 2014)
The typical bone density patterns in the proximal femur can be explained using bone remodeling simulations incorporating a load-adaptive response. Yet, subject-specific variations in bone density have not received much attention. Therefore, the objective of this study was to quantify to what extent subject-specific bone geometry and subject-specific musculoskeletal loading affect the predicted bone density distribution. To accomplish this goal, a computational bone remodeling scheme was combined with gait analysis and a subject-specific musculoskeletal model. Finite element models incorporating the subject-specific geometry as well as the subject-specific hip contact forces and associated muscle forces were used to predict the density distribution in the proximal femur of three individuals. Next, the subject-specific musculoskeletal loads were interchanged between the subjects and the resulting changes in bone remodeling of the proximal femur were analyzed. Simulations results were compared to computed tomography (CT) image-based density profiles. The results confirm that the predicted bone density distribution in the proximal femur is drastically influenced by the inclusion of subject-specific loading, i.e. hip contact forces and muscle forces calculated based on gait analysis data and musculoskeletal modeling. This factor dominated the effect of individualized geometry. We conclude that when predicting femoral density distribution in patients, the effect of subject-specific differences in loading conditions of the hip joint and the associated difference in muscle forces needs to be accounted for. •Bone remodeling scheme was combined with gait analysis.•Subject-specific musculoskeletal loads were applied in finite element simulations.•Interchanging the load cases has a marked effect on the density distribution.•Density distribution in femur is greatly influenced by the subject-specific loading.•Subject-specific differences in loading of the hip joint need to be accounted for.